Calibration of the Qibla Direction for Places of Worship Modern Cafe in Sungai Penuh City - Zahira, Nisha; Darlius, Darlius; Susanti, Susi; Arzam, Arzam (AL-MUTSLA, 2025)
Qibla direction calibration is an effort to ensure the accuracy of the correct qibla direction. This study aims to determine the accuracy of the qibla direction indicated in various cafes in Sungai Penuh City by comparing it precisely with the correct direction through accurate geographical measurements and to examine the Islamic legal perspective on the accuracy of the qibla direction that does not point exactly to the Kaaba or causes deviation in performing prayers. This research is qualitative research with descriptive analysis, which describes the position of the qibla direction of each cafe before calibration and after this research was conducted, so that new findings on the true qibla direction were obtained. The primary data source was five pieces of initial qibla direction data from modern cafes in Sungai Penuh City that were found directly. The data collection techniques used were field observation and documentation. The results of this study found that the qibla direction of five cafes in Sungai Penuh City were all deviated from the correct direction, namely Shifa Donat 3°, Dapoer Qdoes 4°, Cafe Dapur Bunda 11°, Cafe Syahamma 17°, and Puji Sera 28°. Meanwhile, according to experts, a mosque/prayer room is considered accurate if the direction of the building does not deviate more than 2° from the direction of the Kaaba. A deviation of 0° 6' 36“ and -0° 10' 12” from the position of the Kaaba is the permissible limit for facing the qibla in Indonesia, and the magnitude of the qibla direction deviation is only 6 arc minutes.